Can Management Control Systems be applied in SME? A case study of small manufacturing in Indonesia - Marko Hermawan; Jesica Triana Putri (The Indonesian Journal of Accounting Research, 2018)
Abstract: Management control systems (MCS) consists of general measures human capital and performance management that provide an appropriate guideline to improve a company's performance and management control, and budgeting issues. In conducting the research, deep understanding in management control system theory, Chinese and Javanese values in doing business, and characteristics of small-medium family business is highly essential. The paper analyzes the extent to which MCS enables to identify performance, as well as human resource issues, in conjunction with management control in a small manufacturing company. In a particular setting such as Indonesia, other components, such as cultural context, collectivism, leadership, and ethnic group, contribute into an essential factor in MCS. An enterprise such as PT. GAA illustrates various issues as a small manufacturing business, that closely related to family business and cultural dimensions. It is believed that even a generic MCS has little implication towards its performance improvement. However, most of the literature that scrutinize Indonesian SME found that the socio-economic milieu influence more than the procedural systems designed by the theory. Abstrak: Sistem pengendalian manajemen (SPM) terdiri dari ukuran umum modal manusia dan manajemen kinerja yang memberikan pedoman yang tepat untuk meningkatkan kinerja perusahaan dan kontrol manajemen, dan masalah penganggaran. Dalam melakukan penelitian ini, pemahaman yang mendalam dalam teori sistem pengendalian manajemen, nilai-nilai Cina dan Jawa dalam melakukan bisnis, dan karakteristik usaha keluarga kecil menengah sangat penting. Paper ini menganalisis sejauh mana SPM memungkinkan untuk mengidentifikasi kinerja, serta masalah sumber daya manusia, dalam hubungannya dengan pengendalian manajemen di sebuah perusahaan manufaktur kecil. Dalam pengaturan tertentu seperti Indonesia, komponen lain, seperti konteks budaya, kolektivisme, kepemimpinan, dan kelompok etnis, berkontribusi menjadi faktor penting dalam SPM. Perusahaan seperti PT. GAA menggambarkan berbagai masalah sebagai bisnis manufaktur kecil, yang terkait erat dengan dimensi bisnis dan budaya keluarga. Dipercaya bahwa bahkan SPM generik memiliki sedikit implikasi terhadap peningkatan kinerjanya. Namun, sebagian besar literatur yang meneliti UKM